2020
DOI: 10.1186/s12882-020-02034-x
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and risk factors for chronic kidney disease of unknown cause in Malawi: a cross-sectional analysis in a rural and urban population

Abstract: Background An epidemic of chronic kidney disease of unknown cause (CKDu) is occurring in rural communities in tropical regions of low-and middle-income countries in South America and India. Little information is available from Southern African countries which have similar climatic and occupational characteristics to CKDu-endemic countries. We investigated whether CKDu is prevalent in Malawi and identified its potential risk factors in this setting. Methods We conducted a cross-sectional study from January–Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
0
13
2
3
Order By: Relevance
“…The prevalence of CKD without hypertension and diabetes mellitus was approximately 36% in our study, while it was much lower in studies in Malawi (0.2%) and India (1.6%). Even though participants with proteinuria were excluded from the mentioned studies, our finding was more than expected(34,35).…”
Section: Discussioncontrasting
confidence: 51%
“…The prevalence of CKD without hypertension and diabetes mellitus was approximately 36% in our study, while it was much lower in studies in Malawi (0.2%) and India (1.6%). Even though participants with proteinuria were excluded from the mentioned studies, our finding was more than expected(34,35).…”
Section: Discussioncontrasting
confidence: 51%
“…A CKDu study conducted among 821 individuals in Malawi estimated the point prevalence at 0.5%. 40 Eight studies reported on CKD burden attributable to CKDu were identified, including 21 871 individuals (Table 1). A community-based study among 320 participants in Cameroon reported that 42.3% of CKD patients were diagnosed as CKDu, and the patients were all with CKD Stage 3.…”
Section: Epidemiology Of Ckdumentioning
confidence: 99%
“…50 It is also estimated that, in rural Africa, CKDu might account for a larger proportion of the total CKD burden. 28,40,[42][43][44] In rural East Africa, for example, CKDu comprise 66% of the total CKD burden. 42 Additional studies from a rural environment in Nigeria and Tanzania have reported a higher CKD prevalence of 12.4%-27.6% not associated with diabetes, hypertension, obesity or HIV, a proxy for CKDu.…”
Section: Ckd and Environmental Stressorsmentioning
confidence: 99%
“…[ 1 , 2 ] It is mainly caused by diabetes, hypertension, and glomerulonephritis. [ 3 , 4 ] Initially, the symptoms of CKD are insidious and then presented with fatigue, swelling legs, dizziness, and loss of appetite gradually. After stage 3, the above symptoms become more obvious, with increased risks of hypertension, heart failure, bone disease, anemia, gastrointestinal symptoms, and a progress to end-stage kidney failure without proper intervention and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a progressive and irreversible loss of kidney function, with an increased prevalence in recent years [1,2] . It is mainly caused by diabetes, hypertension, and glomerulonephritis [3,4] . Initially, the symptoms of CKD are insidious and then presented with fatigue, swelling legs, dizziness, and loss of appetite gradually.…”
Section: Introductionmentioning
confidence: 99%